Тhe TEN YEARS SINCE THE ADOPTION OF THE LAW ON EXECUTION OF SANCTIONS AND MEASURES OUTSIDE OF THE PENITENTIARY INSTITUTIONS: 1 - Milić, Ivan; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The criminal sanctions that do not entail deprivation of liberty of a perpetrator of a criminal act have been increasingly proscribed. Also, the sentence of imprisonment has been modified in regard to the place of its execution – because it can be conducted either in a correctional facility or in a home of a convicted person.  It is evident that there is the increase of the security measures. In reference to the proscribing the sanctions, there is a similar tendency in the field of misdemeanors as well. If a penatly sanction is imposed and a judicial decision, by the rule, becomes final than follows the execution of a sanction. Тhe process of execution of criminal sanctions has been regulated by a number of documents of different legal strenght – by laws and by-laws. By the year 2014 ’the main regulation’ in the field of execution of criminal sanctions has been the Law on Execution of Criminal Sanctions and by-laws adopted on the basis of the afore mentioned Law. In 2014 the National Assembly adopted the Law on Execution of Sanctions and Measures Outside of the Penitentiary Institutions, by which the above mentioned Law has been supplemented. By the former Law, many important innovations regarding the execution of certain sanctions imposed on the perpetrators of punishable acts: criminal offences, misdemeanors and commercial offences. The execution of certain measures toward a suspected, accused or convicted person has been also regulated by the mentioned Law. It can be concluded that the Law on Execution of Sanctions and Measures Outside of the Penientiary Institutions is a lex specialis in relation to the Law on Execution of Criminal Sanctions.